Advance of Urochloa decumbens (Stapf) R.D. Webster (Poaceae) on remaining native forest in the Serra da BODOQUENA NATIONAL PARK - Dias de Oliveira, José Guilherme (2020)
The replacement of native forest by exotic grasses for pasture formation is a process that involves habitat destruction followed by the introduction of invasive alien species. The Serra da Bodoquena National Park covers an area of 77,021.58ha, comprising natural forests and remnants of abandoned pastures, which represent a threat to local biodiversity conservation. This study analyzed the dynamics of Urochloa decumbens-dominated matrix on remnants of native Deciduous Seasonal Forest within the Park, over 35 years, using satellite images, evaluating natural regeneration trend. The Urochloa matrix covers 1,268.9 (36.9%) of the 3,434.50 hectares study area. Our results indicate that the Urochloa matrix expanded over the native forest remnants, likely due to the occurrence of fire close to the forest edges, which may help natural regeneration failing. 8 months after a fire in 2013, the area of the grass-dominates matrix was found to replace 203.1 hectares over the forest. In this context, restoration actions are demanded, especially those that target fire control.